ANALYSIS INVESTIGASI FORENSIK OPTICAL DISC MENGGUNAKAN STANDAR NIST (NATIONAL INSTITUTE OF STANDARDS AND TECHNOLOGY) - Salam, Fajar Mayda; Muthohirin, Bashor Fauzan; Sari, Zamah (CV SWA Anugerah, 2025)
Digital forensic investigation is a crucial process in collecting, analyzing, and presenting digital evidence that can be used in law enforcement. One type of storage media that is often used as an object of investigation is optical drives, such as CDs, DVDs, and Blu-rays. This study discusses the application of the National Institute of Standards and Technology (NIST) standard method in the forensic analysis of optical drives. The methodology used includes the stages of identification, acquisition, analysis, and reporting, all of which are in accordance with NIST guidelines. Through the application of the NIST method, this study highlights the reliability and accuracy of the procedure in ensuring the integrity of digital evidence from optical drives. This study also discusses challenges that are often faced in the forensic process, such as physical damage to the media and data encryption. The results of the study show that a systematic approach based on NIST standards can improve the accuracy and validity of the investigation results. Thus, the application of this standard is very important to support the credibility of digital evidence in court. Investigasi forensik digital merupakan proses krusial dalam pengumpulan, analisis, dan penyajian bukti digital yang dapat digunakan dalam penegakan hukum. Salah satu jenis media penyimpanan yang sering dijadikan objek investigasi adalah optical drive, seperti CD, DVD, dan Blu-ray. Penelitian ini membahas penerapan metode standar National Institute of Standards and Technology (NIST) dalam analisis forensik optical drive. Metodologi yang digunakan mencakup tahapan identifikasi, akuisisi, analisis, dan pelaporan, yang semuanya sesuai dengan pedoman NIST. Melalui penerapan metode NIST, penelitian ini menyoroti keandalan dan ketepatan prosedur dalam memastikan integritas bukti digital dari optical drive. Studi ini juga membahas tantangan yang sering dihadapi dalam proses forensik, seperti kerusakan fisik media dan enkripsi data. Hasil penelitian menunjukkan bahwa pendekatan sistematis berdasarkan standar NIST mampu meningkatkan akurasi dan validitas hasil investigasi. Dengan demikian, penerapan standar ini sangat penting untuk mendukung kredibilitas bukti digital di pengadilan.